Regional quantification of metabolic liver function using hyperpolarized [1-13C] pyruvate MRI - Uffe Kjaergaard; Andrea Lund; Mohsen Redda; Mattias Hedegaard Kristensen; Malene Aastrup; Nikolaj Bøgh; Kim Sivesgaard; Michael A. Ohliger; Daniel B. Vigneron; Lotte Bonde Bertelsen; Aage Kristian Olsen Alstrup; Esben Søvsø Szocska Hansen; et al. (Scientific Reports)
Abstract Assessment of liver function is essential before partial hepatectomy to predict the risk of post hepatectomy liver failure, a severe and life-threatening complication. Traditional methods have focused on expected future liver remnant (FLR) volume estimation. However, liver volume does not always correlate with function. We suggest that metabolism might be a better surrogate for function than volume. Therefore, we aimed to investigate the metabolic changes in a porcine model of partial portal vein ligation (PVL) using hyperpolarized magnetic resonance imaging (HP-MRI). Specifically, we sought to quantify and compare the pyruvate metabolism in the FLR and the deportalized liver (DL). Six pigs underwent PVL. HP-MRI with [1-13C] pyruvate was performed at baseline, post-surgery, and 1 week after surgery. Metabolic conversion was quantified with kinetic modelling of the rate constants of pyruvate to lactate (kPL) and pyruvate to alanine (kPA). Mean kPL was increased in FLR compared to DL at post-surgery and 1 week after surgery (P = 0.002), while kPA was unaltered (P = 0.761). These findings indicate a metabolic shift towards glycolysis in the FLR. This non-invasive metabolic imaging technique could serve as a powerful tool for evaluation of regional liver function prior to partial hepatectomy and consequently improve patient outcomes.